EFEKTIFITAS KOMUNIKASI PNPM MANDIRI DENGAN PEMANFATAN KEARIFAN LOKAL DALAM PENGENTASAN KEMISKINAN DI KOTA PADANG - M. Mochtar Mas’od; Ahmad Maulana Anshori; Teguh Ansori; Muhammad Haris; Malik Ibrahim (Nusantara Hasana Journal, 2024)
Research on the Communication Approach with the Utilization of Local Wisdom in Poverty Alleviation in Padang City is conducted as part of the National Community Empowerment Program in West Sumatra Province. The purpose of this research is to describe, explain, and analyze how knowledge-based communication is applied in poverty eradication efforts. The research method used is qualitative descriptive method. The results of the research show that community empowerment programs actively utilize the basic concepts of human values, such as honesty, solidarity, volunteerism, and integrity. These concepts are closely related to norms and values that have become an integral part of the local community. In addition, the local wisdom inherent in the community in the research area is also utilized by the neighborhood facilitators in implementing the program activities. With this approach, community empowerment programs in Padang City tap into local wisdom as the main foundation. This aims to build more effective and relevant communication with the needs and values believed by the local community. This approach strengthens the effectiveness of poverty alleviation programs by aligning communication strategies with the realities and local wisdom of the community.